RETRACTED: INNOVATION ACTIVITIES: INDICATORS AND IMPLEMENTATION METHODS - A. L. Gaponenko; S. V. Pirogov; I. F. Chernyavski (Модернизация, инновация, развитие)
Retracted articleInnovation is a new development in the field of technology, work organization or management that provides for increased efficiency. Today, the innovation process has become nonlinear. It is important for an innovation-based economy to create something new, but it is more important to make productive use of innovations. In recent years, modern tools have emerged and continue to develop in the national innovation policy, but they are not exhaustive of the national innovation system. By many indicators of innovation activities, Russia is far behind the world average. Recently, crowdsourcing (transfer of tasks to large groups of people in the form of an open offer) has become a powerful innovation tool.